Gastric Duplication Cyst with Macroscopic Serosal Heterotopic Pancreas - Sinha, Anindita; Saluja, Sundeep S; Gamanagatti, Shivanand (JOP. Journal of the Pancreas, 2010)
Context Gastric duplication cysts are often associated with microscopic evidence of ectopic pancreatic tissue on their submucosal surface and, less commonly, on the subserosal surface. Case report We present an unusual case of a gastric duplication cyst with finger-like projections and a large heterotopic pancreas on the serosal surface of the cyst in a 30-year-old female. Conclusion We point out the unusual imaging findings which helped in the preoperative diagnosis. Image: A two-layered pattern of the wall of the duplication cyst.